A lipid-soluble extract of Pinellia pedatisecta Schott enhances antitumor T cell responses by restoring tumor-associated dendritic cell activation and maturation. (15th September 2019) - Wang, Yumeng; Huang, Haixia; Yao, Sheng; Li, Guiling; Xu, Congjian; Ye, Yang; Gui, Suiqi
Abstract: Ethnopharmacological relevance: Pinellia pedatisecta Schott (PPS)is a traditional Chinese medicine functioning as reducing swelling and drying dampness. Pinellia pedatisecta Schott extract (PE) has been confirmed to suppress cervical tumor growth and modulate the antitumor CD4 + T helper immunity towards Th1. Aims: To explore the roles of PE in modulating tumor-associated dendritic cell (TADC) activation and function. Methods: For in vivo studies, HPV + TC-1 mouse tumor models were conducted and treated with PE for 3 weeks (10 mg/kg/d or 20 mg/kg/day). The immune profiles of spleen, tumor-draining lymph nodes (TDLNs), tumor and serum were analyzed by flow cytometry and multiplexed bead-based immunoassay. For in vitro studies, TADCs were generated by tumor-conditioned medium and treated with PE solution. The maturation and function of TADCs were evaluated by flow cytometry, ELISA, mixed lymphocyte reaction (MLR) and cytotoxic T lymphocyte (CTL) assay. Furthermore, the effect of PE on SOCS1 pathway was examined by western blotting and real time PCR. Results: PE upregulated the expression of major histocompatibility complex class II (MHCII) and costimulatory molecules CD80 and CD86 on TADCs and promoted IL-12 secretion from TADCs. In addition, PE-treated TADCs promoted the proliferation of CD4 + and CD8 + T cells and induced the differentiation of IFN-γ + CD4 + and GZMB + CD8 + T cells. PE-treated TADCs also elicited a more powerful antigen-specific cytotoxic T lymphocyte (CTL) response. Furthermore, PE treatment in vivo enhanced the proliferation, activated the functional ability (increased Ki67, CD137, GZMB or IFN-γ, TNF-α expression) and reversed the exhaustion (impaired CD95 or PD-1 expression) of antitumor T cells. Mechanistically, PE inhibited SOCS1-restrained JAK2 activation in TADCs. Conclusions: PE efficiently restored the immature status of TADCs and enhanced their function as antigen-presenting cells to further elicit antitumor Th1 and CTL responses, suggesting that PE may be a potential immunomodulatory drug for cancer treatment. Graphical abstract: Image 1